AWARENESS AND KNOWLEDGE OF PARENT CHILD INTERACTION THERAPY AMONG SPEECH LANGUAGE PATHOLOGISTS IN PAKISTAN - Humaira Qayyum; Soabah Wasim (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background and Objective: It is commonly observed that speech language pathologists conduct sessions with children having speech, language and communication difficulties in the absence of parents in Pakistan. The objective of the research was to determine awareness and knowledge of Parent Child Interaction Therapy among Speech Language Pathologists in Pakistan. Methods: The study was a descriptive cross-sectional study. The study included 134 speech and language pathologists according to 95% Confidence Interval. The study was conducted through a self-developed questionnaire regarding Parent Child Interaction Therapy based on literature review and expert’s opinion. Speech language pathologists having at least 1 years’ experience of dealing with children having speech and language disorders were included from all over Pakistan through online google form shared in multiple Facebook and WhatsApp groups of SLPs. The data was analyzed by descriptive statistical techniques i.e. frequency, percentages and cross tabulation through SPSS 27. Results: The data analysis revealed that 44% of the speech language pathologists strongly agreed and 44% agreed regarding having awareness about Parent child interaction therapy. However, 78.4% of the participants scored low, 14.9% scored moderate and only 6.7% scored high on the knowledge scale of PCIT. Conclusion: A huge disconnect was visible between the awareness of parent child interaction therapy claimed by the majority of participants while the majority of them lack adequate knowledge for it